Balinese Community Perceptions of The Use of Balinese Script on Merchandise Products: An Analysis of Aesthetics, Ethics, And Cultural Desacralization (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Balinese script is an intangible cultural heritage with historical, aesthetic, and spiritual value. In recent years, it has been utilized in merchandise design to strengthen Balinese cultural identity within the creative industry. However, its commercial use has sparked debates regarding ethics and public perception. This study examines public views on the use of Balinese script in merchandise design through surveys and interviews involving both younger and older generations of Balinese society. The findings show that the younger generation supports its use as a means of cultural preservation, while the older generation emphasizes ethical considerations, particularly concerning sacred characters such as Ongkara and Modre, which should not be used carelessly. The Balinese script is regarded as visually appealing but requires cultural education and respect for local norms. The study concludes that the Balinese script holds great potential in the merchandise industry if applied wisely